Legal protection of religious freedom in Australia - Evans, Carolyn [ (Carolyn Maree)] (Federation Press, 2012)
This book brings together into a single volume, a wealth of information and insight that will appeal both to professional who need to deal with religious issues in a legal context and also the reader who is interested in the role of religion in Australian law and society